Sport event attributes influencing sport tourists' attendance at sepak takraw event - Zarei, Azadeh; Holmes, Kirsten; Yusof, Aminuddin (Cognizant Communication Corporation, 2018)
The use of traditional sports events as modern sport tourism products has grown rapidly over recent decades. This article investigated differences in sport attributes that influence sport tourists' behavioral choices for attending a sepak takraw event using the human and nucleus component of Leiper's tourism attraction system. The study uses a sample of 316 sport tourists including domestic sport tourists (n=224) and foreign sport tourists (n=92) attending ISTAF Super Series. The findings reveal different factors were important to domestic sport tourists compared to foreign sport tourists. Domestic respondents reported that sport event attributes such as convenience and accessibility, game attractiveness, and sport facility were important in their decisions to attend a sepak takraw event while foreign sport tourists perceived cost to be a necessary sport attribute for their attendance. This article provides support for a sepak takraw as an event product that offers new sport marketing opportunities for particular target market segments within small-scale sport tourism.